ANCAMAN BAHASA GAUL DI ERA MODERN TERHADAP BAHASA ASLI DI INDONESIA - Qomarsha, Deniswa; Defiyah, Areza Puspita (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Language is the identity of a country or region that is used as the main means of communication. The use of slang in this modern era has become common among Indonesian teenagers. However, the use of slang raises concerns about the existence of the Indonesian language as a national cultural heritage. The use of slang is not only used by teenagers. In fact, educated people also use this slang in oral and written forms, in formal and non-formal times, which results in the use of language that is not good and correct. In addition, the use of slang can also change the mindset and attitude of society towards the Indonesian language which is the official language of the country. It would be nice if we could use good and correct Indonesian, so that the existence of the Indonesian nation as a national language is maintained. Indonesian is the language of unity, therefore as Indonesian people we must care about and respect the national language and also help maintain and preserve our language, namely Indonesian.